Hydrodynamic Model for Operational Forecasting in Coastal Waters of Ghana - Felix, Uba; Essandoh, Eric Osei; . Nyantakyi, Emmanuel K (Open Journal of Modelling and Simulation, 2020)
The provision of economic resources to countries at the shore of Gulf of Guinea is a very important effort that has helped West Africa to develop to some extent. Taking the study area as a system it will be important to know the dynamics that occur in it to help neighouring countries predict its physical and thermodynamics states at all times. Ghana is located in West Africa and it is bordered in the south by the Gulf of Guinea or Atlantic Ocean. The objective of this research is to characterize the hydrodynamic circulation of the Gulf of Guinea areas neighouring Ghana. A 3-Dimensional hydrodynamic model was implemented in the territorial waters of Ghana using the Mod elo Hidrodinâmico, MOHID model to represent the dynamics and study the complex circulation pattern of the sea. To achieve this in an affordable computational time, nested domain approach was used to implement the hydrodynamic model in both 2 and 3-Dimensional gridded levels. The first level is a barotropic model with only tide. The nested domains of the rest of the levels are baroclinic forced with atmospheric and oceanic elements. To quantify its accuracy, the model was validated and calibrated in three stages; first, the frequency of the water level, followed by the circulation pattern and last, analysing the nature and profiles of the atmospheric and oceanic elements. The implemented model showed good agreement with the measured water surface level in the domain with mean error values not exceeding 14.00% of the measured data and with correlation factors higher than 0.80. Also, the intensity and direction of velocity observed in the current data are well represented by the model at the water surface levels with mean errors lower than 20.00% of the measured data components. The profiles obtained for both the temperature and salinity at shore show completely a straight line for salinity and also a straight line which is slightly curved at the top for the temperature profile. The vertical straight line for the salinity profile shows that at the shore the waters are not stratified vertically or they are well mixed. The slight curve at the top of the temperature graph accounts for the mixing dynamics that occur close to land or the effect of heat flux at the surface. It can be concluded that the hydrodynamic model obtained by this study is the true reflection of the territorial waters of Ghana
Keywords: Ghana; Gulf of Guinea; Oceanic Circulation; Hydrodynamic; MOHID; University of Energy & Natural Resources; ACE: Energy and Environmental Sustainability; power; Prosper Anumah